การออกแบบไซโคลนสำหรับอนุภาคของแข็งในฟลูอิไดซ์เบดแบบหมุนเวียน - ณัฐพงศ์ อิ่มแสงจันทร์ (จุฬาลงกรณ์มหาวิทยาลัย, 2010)
Cyclone is an essential part of a circulating fluidized bed (CFB) combustor in collecting the uncombusted particulates before sending back to the system for reburning. This research studied the effectiveness of three different cyclones namely: conventional cyclone and two types of square cyclones. The experiment in CFB reactor and the computation fluid dynamics (CFD) were carried out. The CFB reactor has 0.10 meter in diameter and 6.0 meters height. All cyclones has diameter of 0.16 meter. The three main parameters were studied: shape of cyclone, primary air flow rate and density of particles. Primary air flow rate were varied from 175 to 230 m3/h. Sand and mixed sand and coal with different size and density are used. The CFD results show that the efficiencies of conventional and square cyclones were similar, 99 percent approximately, under the same condition (10.9 to 15.0 m/s of inlet velocity and 68.6 to 147.0 Pascal of pressure drop). For experimental results, pressure drop increased when primary air flow rate raised. Pressure drop in both square cyclones is lower than conventional cyclone in the range of 20 to 50 Pascal. Consequently, the square cyclone actual condition getting form the experimental results were used to simulate the efficiency again. The result can be concluded that the computational efficiency was consistent with the experimental efficiency. The efficiency of squared cyclone was lower than conventional cyclone. It also found that the size of the solid outlet of square cyclone influence on the decreasing of collection efficiency of cyclone.